DEVELOPING THE ENTREPRENEURSHIP INCUBATOR MODEL TO INCREASE STUDENTS INDEPENDENCE OF ENTREPRENEURSHIP MENTALITY - Suranto, Suranto; Rahmawati, Rahmawati (Journal of Indonesian Economy and Business, 2013)
This research aims to develop a model of entrepreneurial incubator for students inentrepreneurship learning. The model developed by the incubator includes: the empowermentof learners, the concept of problem, problem solution, through the structure of the incubatormodels doing, empowering, facilitating, and evaluating.This research was a research and development. The steps taken in the development ofthe model were: (1) designing a model, designing questionnaires, and validating themodel, by measuring the goodness of fit; (2) testing the model to measure the appliedmodel. In model validation, the data were collected from 130 students who got incubatortreatment selection using the simple random sampling technique. The instrument used fordata collection was a questionnaire. The data were analysied using the concept of SEM(Structural Equation Modeling). The method used in experimental field trials was the experimentalgroup and control group (pretest-posttest control group design). The subjectsof the tryout were 75 students of informatics engineering course who were not the subjectsof the incubator program (the control group) and 75 students of chemistry education,chemistry, mathematics education, mathematics, biology education, and biology were referredto as the experimental group (program subject to the incubator). The data werecollected through interviews and questionnaires. The data were analyzed using t-test trialsto find out a significant difference in the behavior of the experimental group and controlgroup.The results of the study of the entrepreneurship incubator model development is otherwisevalid according to the probability (p) 0.0685, Goodness of Fit Model (GFI) 0.8256,Adjusted Goodness of Fit Index (AGFI) 0.7706, Comparative Fit Index (CFI) 0.9883, andthe Root Mean Square Error of Approximation (RMSEA) 0.054. This model is consideredeffective because it can increase the independence of learners. The result of the confirmatoryanalysis (CFA) shows that each latent variable is proved to be formed by the manifestsof one dimension. The model is applied to have a positive impact on enhancing thestudents tendency in mental independence, after receiving treatment assistance incubators.Latent variable-power is reflected by the manifest: (a) the technical capabilities in writing,(b) awareness for entrepreneurship, (c) motivation for entrepreneurship, (d) the excess ofself to self-employed, (e) the lack of self to self-employed, (f) access to other party toentrepreneurship, and (g) networking for entrepreneurship. While professionals have amanifest latent variables: (a) believing in themselves to entrepreneurship, (b) being independentfor entrepreneurship, (c) being resilient and determined to entrepreneurship, (d)perseverance up to entrepreneurship, (e) writing creatively on entrepreneurship. Manifestvariables in the form of mental self-reliance has increased after the mentoring model ofentrepreneurial incubator. This suggests that the better the model of mentoring incubator,the better it will form a mental model of the entrepreneurial independence.Keywords: models of incubators, entrepreneurship, independence, students.